Decolonising Higher Education in the Era of Globalisation and Internationalisation - Fomunyam, Kehdinga George (UJ Press, 2019)
Conceived within a context of transdisciplinarity and pluriversalism, and in rigorous response to the Eurocentric, globalising and nationalising structures of power that undergird and inhabit contemporary praxis in higher education - especially in African higher education - this collection of essays brings to the on-going discourse on decolonisation fresh, rich, probing and multilayered perspectives that should accelerate the process of decolonisation, not only in higher education in Africa, but also in the global imaginary. A remarkable, courageous and potentially revolutionary achievement, this book deserves a special place on curricula throughout the world of higher education.